Evaluation of Anti-amoebic Activity of Spring Leaf Extract of Artemisia Aucheri on Acanthamoeba (T4 strain) In vitro - KarimiPourSaryazdi, Amir; KarimiPourSaryazdi, Yeganeh; Ghaffarifar, Fatemeh; Ahmadi, Maryam; Zaki, Leila (Anti-Infective Agents, 2021)
Background: Acanthamoeba belongs to the free-living amoebae genus that causes a widespread infection with different severities in humans and animals. Treatment of these opportunistic protozoan infections is still not safe or effective. The aim of the present study was to evaluate the effect of spring extract of Artemisia aucheri on Acanthamoeba in vitro. Methods: Trophozoites and cysts of Acanthamoeba were cultured on non-nutrient agar plates containing bacteria Escherichia coli. Macrophage cells were cultured in RPMI-1640 medium. Different concentrations of spring extracts of A. aucheri were added to cultivated parasites and macrophages and additionally calculated to determine the 50% inhibitory concentration (IC50) for parasites and 50% cytotoxic concentration (CC50) for macrophages. Then, the viability of parasites were evaluated using counting assay. MTT assay was carried out on macrophage cells based on growth inhibition. Furthermore, in order to determine the possible induction of apoptosis in cysts of Acanthamoeba, flow cytometry method was employed using annexin staining. Results: The effect of A. aucheri on trophozoites and cysts of Acanthamoeba was effective and had a reverse relationship with its concentration. The IC50 value of spring extract on trophozoites and cysts of the parasite was estimated to be 200 and 333 μg/ml at 24 h, respectively. According to the results of flow cytometry, the spring A. aucheri extract caused about 20% apoptosis. Conclusion: Regarding the above results, it can be concluded that spring A. aucheri extract was effective against trophozoite and cyst forms of Acanthamoeba in vitro. Therefore, this plant could be an appropriate herbal drug candidate for the treatment of Acanthamoeba infections.
Keywords: acanthamoeba